Accuracy of Pedicle Screw Placement and Clinical Outcomes of Robot-assisted Technique Versus Conventional Freehand Technique in Spine Surgery From Nine Randomized Controlled Trials: A Meta-analysis - Li, Hui-Min; Zhang, Ren-Jie; Shen, Cai-Liang (Spine (Philadelphia, Pa. 1976), 2020)
A meta-analysis. To investigate whether robot-assisted techniques are superior to conventional techniques in terms of the accuracy of pedicle screw placement and clinical indexes. Robot-assisted techniques are increasingly applied to spine surgery to reduce the rate of screw misplacement. However, controversy about the superiority of robot-assisted techniques over conventional freehand techniques remains. We conducted a comprehensive search of PubMed, EMBASE, and Cochrane Library for potentially eligible articles. The outcomes were evaluated in terms of risk ratio (RR) or standardized mean difference and the associated 95% confidence intervals (CIs). Meta-analysis was performed using the RevMan 5.3 software and subgroup analyses were performed based on the robot type for the accuracy of pedicle screw placement. Nine randomized controlled trials with 696 patients were included in this meta-analysis. The results demonstrated that the robot-assisted technique was more accurate in pedicle screw placement than the freehand technique. Subgroup analyses showed that the TINAVI robot-assisted technique was more accurate in screw positions Grade A (RR, 1.10; 95% CI, 1.06-1.14), Grade B (RR, 0.46; 95% CI, 0.28-0.75), and Grades C + D + E (RR, 0.21; 95% CI, 0.09-0.45) than the freehand technique, whereas the Renaissance robot-assisted technique showed the same accuracy as the freehand technique in screw positions Grade A, Grade B, and Grades C + D + E. Furthermore, the robot-assisted techniques showed equivalent postoperative stay, visual analogue scale scores, and Oswestry disability index scores to those of the freehand technique and shorter intraoperative radiation exposure time, fewer radiation dose and proximal facet violations but longer surgical time than the freehand technique. The robot-assisted technique is more accurate in pedicle screw placement than the freehand technique. And TINAVI robot-assisted pedicle screw placement is a more accurate alternative to conventional techniques and the Renaissance robot-assisted procedure. 1.